Effects of cold-water immersion on physical performance between successive matches in high-performance junior male soccer players - Rowsell, G. J.; Coutts, A. J.; Reaburn, P.; Hill-Haas, S. (Journal of Sports Sciences, 2009)
In this study, we investigated the effect of water immersion on physical test performance and perception of fatigue/recovery during a 4-day simulated soccer tournament. Twenty high-performance junior male soccer players (age 15.9 ± 0.6 years) played four matches in 4 days and undertook either cold-water immersion (10 ± 0.5°C) or thermoneutral water immersion (34 ± 0.5°C) after each match. Physical performance tests (countermovement jump height, heart rate, and rating of perceived exertion after a standard 5-min run and 1220-m repeated sprint test), intracellular proteins, and inflammatory markers were recorded approximately 90 min before each match and 22 h after the final match. Perceptual measures of recovery (physical, mental, leg soreness, and general fatigue) were recorded 22 h after each match. There were non-significant reductions in countermovement jump height (1.7-7.3%, P = 0.74, ny2 = 0.34) and repeated sprint ability (1.0-2.1%, P = 0.41, ny2 = 0.07) over the 4-day tournament with no differences between groups. Post-shuttle run rating of perceived exertion increased over the tournament in both groups (P < 0.001, ny2 = 0.48), whereas the perceptions of leg soreness (P = 0.004, ny2 = 0.30) and general fatigue (P = 0.007, ny2 = 0.12) were lower in the cold-water immersion group than the thermoneutral immersion group over the tournament. Creatine kinase (P = 0.004, ny2 = 0.26) and lactate dehydrogenase (P < 0.001, ny2 = 0.40) concentrations increased in both groups but there were no changes over time for any inflammatory markers. These results suggest that immediate post-match cold-water immersion does not affect physical test performance or indices of muscle damage and inflammation but does reduce the perception of general fatigue and leg soreness between matches in tournaments.